The economic determinants of the number of minority farmers in the southern region of the United States, 1969-1997 - Luster, Tonshia (Kansas State University, 2009)
The primary purpose of this research was to identify and quantify the determinants of the number of minority farms in the Southern region of the United States during the time period, 1969-1997. A second objective was to determine the impact of globalization and international trade agreements on the number of African-American farmers in the Southern region of the United States. Regression results indicate that minority farm labor was responsive to the returns to agriculture labor relative to nonfarm labor returns, as well as to cotton and rice prices. Increase in the cotton price increased minority farmer income, slowing the rate of agricultural migration from the Southern region of the United States. To the extent that globalization results in lower cotton prices, international agricultural trade agreements are likely to result in further movement of minority farmers out of agriculture in the Southern region of the United States.
Keywords: determinants; economic; minority; southern; globalization; international; Agriculture, General (0473)